Homonymous Sectoranopia: Asymptomatic Presentation of a Lateral Geniculate Nucleus Lesion. (2nd November 2015) - Pasu, Saruban; Ridha, Basil H.; Wagh, Vijay; Jindahra, Panitha; Siddiqui, Ata; Plant, Gordon; Stanford, Miles
Abstract: This is a rare presentation of brain tumour in the region of the lateral geniculate nucleus (LGN) presenting as a homonymous horizontal sectoranopia (HHS). The case highlights that subtle field defects can be asymptomatic and only detected by formal perimetry. Although homonymous sectoranopia is a rare form of visual field defect, it should be recognised as a potential manifestation of potentially significant intracranial pathology.